Manajemen Resiko Pembiayaan Bank Syariah Indonesia : Tantangan dan Solusi - Heri Kuncoro Putro; Andriani .; Moh Agus Sifa' (Journal of Islamic Banking, 2025)
Risk management in Islamic financial institutions should be a primary concern. Good risk management can help Islamic banks to identify, measure, manage, and control the risks faced. The study aims to find out more about the challenges faced and the solutions implemented by financial institutions, especially Islamic banking. The research method uses a descriptive qualitative method with data collection through case studies, literature reviews, observations and interviews with related parties. The results of the study show the challenges faced by Islamic banking in risk management in the form of: technology risk, digital security risk, liquidity risk and risk of compliance with Islamic financial principles. Solutions are needed to address the challenges faced, namely, first, implementing the Basel III standard risk management framework, AAOIFI standards and the specific needs of the Islamic fintech ecosystem. Second, providing training and educating human resources.